Mechanics of machinery - Mostafa, Mahmoud A. (CRC Press, 2013)
This text distinguishes itself from related books by offering both graphical and analytical methods for mechanism analysis. The author presents a method that he developed to simplify the application of kinematic analysis. He uses analytical and graphical methods for solving problems and includes simulation software as a graphical interface for various mechanisms. Specific topics covered include mechanisms, velocities and accelerations, cams, spur gears, gear trains, force analysis, balancing, and helical, worm, and bevel gears.